Compatibility Testing of Synthesized TiO2 Nanoparticles on The Fast-Growing Wood Physical Properties - Prihatini, Esti; Ismail, Rohmat; Sekartining Rahayu, Istie; Dwi Laksono, Gilang; Khairunissa, Dhiya (Sains Natural: Journal of Biology and Chemistry, 2024)
Jabon wood (Anthochepalus cadamba) has inferior quality, so it is necessary to modify the wood to improve the quality of its physical properties, namely by impregnating TiO2 nanoparticles (NP-TiO2). This study aims to determine the right synthesis method for the synthesis of NP-TiO2 so as to improve the quality of the physical properties of jabon wood optimally. The results of FTIR testing showed that jabon wood has successfully impregnated NP-TiO2 by hydrothermal and solvothermal methods with ethanol, acetone, and methanol solvents with the identification of the functional group of Ti-O at wavenumber 533 cm-1 and the Ti-O-Ti functional group at wavenumber 679 cm-1 which is the bond formed in the framework of the TiO2 compound. The results of the physical properties test showed that NP-TiO2 which was successfully impregnated into wood was synthesized using hydrothermal and solvothermal methods, namely acetone, methanol, and ethanol, with a WPG value of 1.36%, 2.6%, 2.16%, and 1.61%, respectively. XRD test results show that jabon wood has successfully impregnated NP-TiO2 by hydrothermal and solvothermal methods using acetone, ethanol, and methanol solvents with the identification of anatase TiO2 crystal lattice and crystal sizes of 16.21, 15.94, 14.27, dan 15.75 nm, respectively.